Influence of Temperature and Relative Humidity on the Survival and Longevity of Larvae and Adult Weevils of Patialus tecomella Pajni, Kumar&rose (Coleoptera : Curculionidae) - Sharma, Meeta; Ahmed, S. I. (Indian Forester, 2006)
Tecomella undulata (Sm.) Seem, a member of the family Bignoniaceae, is one of the codominating tree species in the desert forests of Western Rajasthan and adjoining lands of Haryana and Punjab. It is commonly known as" Rohida" or" Marwar teak " due to its sparking features of drought tolerant and high quality of timber. Seedlings and young plantations of T. undulata are frequently severely attacked by a serious curculionid pest, Patialus tecomella throughout the tract of its distribution in arid and semi-arid areas. The objectives of the experiment conducted and reported in this paper are to examine the influence of selected constant temperatures and relative humidities on the longevity of starved larvae and adult weevils and to determine the threshold temperature and humidity ranges for the optimum longevity of P. tecomella, when kept as isolated single individuals and in different group sizes viz., groups of 5, 10 and 20 individuals, under the same experimental conditions. The adults and larvae of P. tecomella survived for a maximum period in groups as well as in isolated individuals at a temperature of 35° ± 0.5°C and 74 ± 5% relative humidity. Minimum survival periods are observed under the temperature of 45° ± 0.5°C and a relative humidity of 10 ± 5% in both the cases. The larvae and the adults (both in groups and as isolated individuals) can tolerate minor desiccation. Both the adults and larvae of P. tecomella survived for a longer period in groups than as isolated individuals.